Struktur Pembentuk Nomina Tempat dalam Bahasa Jepang pada Novel Berjudul Fune wo Amu Karya Shion Miura - Pamungkas, Aji Satrio; Widya Purnawati, Ketut; Rauh Artana, I Nyoman (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 5 No 2 (2023)DO - 10.24843/JS.2023.v05.i02.p11, 2023)
"The Structure of Forming Nouns of Place in Japanese in a Novel Entitled Fune Wo Amu by Shion Miura" is the title of this study. The purpose of this research is to learn more about the structure of the formation of place nouns in Japanese which is found in a novel entitled Fune Wo Amu by Shion Miura. Descriptive qualitative method is the method used in this research. Japanese Morphological Theory and the Semantic Theory by Tsujimura (2014) are the theory used in this research. Based on the result of this research, it can be concluded that noun place marker suffixes can be attached to bound morphemes, nouns, verbal nouns, and root verbs (ren'y?kei). The kango type of word is the type of word that is most often attached by place marking suffixes in Japanese. In addition, when compared to other types of place noun-forming suffixes such as ~ ? (-ba, -jo?), ~ ? (-dokoro, -sho, -jo), ~ ? (-kan), ~ ? (-ya), ~ ? (-chi), ~ ? (-ten), ~ ? (-in), and ~ ? (-do?), the suffix ~ ? (-shitsu) produces the most place nouns.